The mediating and moderating effects of resilience on the relationship between sleep quality and psychological distress in Chinese women with infertility - Zhenhua Jiang; Sen Hou; Yajie Zhang; Liping Zong (BMC, 2024)
Abstract Background Research has widely indicated that the psychological distress experienced by infertile patients during fertility treatments may have a negative effect on the results of assisted reproduction. Although numerous studies have shown that psychological resilience and sleep quality are important influencing factors for psychological distress, the mediating mechanisms of psychological resilience in the relationship between sleep quality and psychological distress for Chinese women in particular remain unclear. Therefore, the current study investigates the association between sleep quality, resilience, and psychological distress in Chinese women with infertility and examines the mediating and moderating roles of resilience on the relationship between sleep quality and psychological distress. Methods In this cross-sectional study, a total of 595 women with infertility who were undergoing IVF-ET were recruited at the Reproductive Medicine, Shandong University, from April to November 2019. Participants were instructed to complete four questionnaires, including a questionnaire about socio-demographic and clinical-related information, the Pittsburgh Sleep Quality Index (PSQI), the 10-item Connor-Davidson Resilience Scale (CD-RISC-10), and the Kessler-10 (K10). Pearson's correlation analysis was conducted preliminarily to describe the relationships between sleep quality, resilience, and psychological distress. A mediation model and a moderated model were constructed and analyzed using the PROCESS macro for SPSS. The Johnson-Neyman (J-N) technique was then used to identify the regions of significance across the levels of moderator values. Results Patients in the sample had a high prevalence of psychological distress (48.6%, K10 scores > 22), and mediation analysis indicated that resilience played a partially mediating role in the relationship between sleep quality and psychological distress (indict effect = 0.072, P < 0.001). Moderation analysis indicated that resilience also moderated the association between sleep quality and psychological distress. Conclusions Resilience may play a key role in the relationship between sleep quality and psychological distress. Our findings imply that resilience training may therefore be an effective component of psychological distress intervention in women with infertility.